2017
DOI: 10.1681/asn.2016111184
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine Contributes to the Impaired Response to Erythropoietin in CKD-Anemia

Abstract: Erythropoietin-resistant anemia is associated with adverse cardiovascular events in patients with ESRD, but the underlying mechanism remains unclear. Here, we evaluated the role of the endogenous nitric oxide synthase inhibitor asymmetric dimethylarginine (ADMA). In 54 patients with advanced CKD, erythrocyte but not plasma ADMA levels independently associated with low hemoglobin values, although levels of both types of ADMA were elevated compared with those in healthy volunteers. Furthermore, erythrocyte ADMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…In the elderly, elevated EPO levels were associated with increased risk of death, and in renal transplant recipients higher endogenous plasma EPO was associated with cardiovascular mortality and all-cause mortality (den Elzen et al, 2010;Sinkeler et al, 2012). Elevated EPO levels may be indicative of EPO resistance resulting from underlying co-morbidities including inflammation, iron status, malnutrition and disrupted NO metabolism (Ganz and Nemeth, 2016;Yokoro et al, 2017). The increase risk of adverse effects with high exogenous EPO administration is exemplified in extreme athletes who use EPO as a performanceenhancing drug.…”
Section: Elevated Epo In Human and Decreasing Obesity Prevalence At Imentioning
confidence: 99%
“…In the elderly, elevated EPO levels were associated with increased risk of death, and in renal transplant recipients higher endogenous plasma EPO was associated with cardiovascular mortality and all-cause mortality (den Elzen et al, 2010;Sinkeler et al, 2012). Elevated EPO levels may be indicative of EPO resistance resulting from underlying co-morbidities including inflammation, iron status, malnutrition and disrupted NO metabolism (Ganz and Nemeth, 2016;Yokoro et al, 2017). The increase risk of adverse effects with high exogenous EPO administration is exemplified in extreme athletes who use EPO as a performanceenhancing drug.…”
Section: Elevated Epo In Human and Decreasing Obesity Prevalence At Imentioning
confidence: 99%
“…Anemia is considered the most frequent complication in patients with end-stage renal disease (ESRD), especially in the subpopulation on maintenance dialysis (1). It has also been identified as an independent risk factor/predictor for major cardiovascular events, including heart failure and atherosclerosis (2).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that up to 10% of patients in the erythropoietin-stimulating agent (ESA)-treated population have a lower erythropoietin response (1,4,5). Furthermore, an imbalance between the production of EPO and the demand for EPO is another pivotal reason for anemia in patients treated with ESA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations